The modernization of the contents and methods of education: Reflections on the new school in Colombia - Ríos Beltrán, Rafael; Cerquera Cuellar, Martha Yanet (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The New School in Colombia meant the opening towards a process of modernization of the contents and of reform of the teaching methods. From a historical perspective, the article describes this process across the methods that produced the main changes in the systems and teaching methods in the Colombian pedagogical knowledge during the first half of the XXth century. To know: the Centers of Interest, of the Belgian doctor Ovidio Decroly and the Project method derived from the active pedagogics of the North American John Dewey. The teachers in development and ex-students made use of these two systems of education to encompass the education and to break with the ancient isolation of the different subjects. Its dissertation or monographs of grade constitute a field documentary invaluable to understand the complexity of the practices of appropriation of this pedagogic event in Colombia.